2022
DOI: 10.1108/jcp-04-2022-0010
|View full text |Cite
|
Sign up to set email alerts
|

Looking at the moral judgments of offenders through new lenses

Abstract: Purpose Studies on the moral judgment of offenders conducted within a neo-Kolhbergian framework found that offenders exhibit more primitive thinking about moral issues compared to nonoffenders. The purpose of this study is to explore, within the mental model theory, the role of reasoning in moral judgments of offenders, considering both similarities and differences with nonoffenders. Design/methodology/approach A series of moral scenarios were randomly presented to both offenders and nonoffenders. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Through a series of experiments, the authors demonstrated that the pleasantness of a moral assertion was positively correlated with the strength of individuals' belief in it. Interestingly, this relationship did not hold true for factual assertions and was observed in both typical and atypical populations (Zara et al, 2022). Given these previous findings, further research is necessary to gain a deeper understanding of the contentious role of negative emotions in mediating the perceived accuracy of fake news.…”
Section: Beyond the Appearance: The Psychology Of Fake Newsmentioning
confidence: 98%
“…Through a series of experiments, the authors demonstrated that the pleasantness of a moral assertion was positively correlated with the strength of individuals' belief in it. Interestingly, this relationship did not hold true for factual assertions and was observed in both typical and atypical populations (Zara et al, 2022). Given these previous findings, further research is necessary to gain a deeper understanding of the contentious role of negative emotions in mediating the perceived accuracy of fake news.…”
Section: Beyond the Appearance: The Psychology Of Fake Newsmentioning
confidence: 98%